1998
DOI: 10.1111/j.1348-0421.1998.tb02350.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Rabies Virus RNA Polymerase: 2. Possible Relationships between the Two Forms of the Non‐Catalytic Subunit (P Protein)

Abstract: We investigated the relationship between the two forms of rabies virus P protein, a non‐catalytic subunit of rabies virus RNA polymerase. The two displayed different electrophoretic mobilities as 37‐ and 40‐kDa polypeptides, hence termed as p37 and p40, respectively. Double labeling experiments with [3H]leucine and [32P]orthophosphate demonstrated that p40 was much more phosphorylated than p37. Treatment of the virion proteins with alkaline phosphatase eliminated only p40, and not 37‐kDa polypeptide. The p37 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…In our previous study (31), p40 was suggested to be a hyperphosphorylated form of P protein based on the observation of its relatively much higher specific radioactivity than that of p37 in the double radiolabeling experiments with [ 32 P]orthophosphate and [ 3 H]leucine. The number of phosphate groups in each p37 molecule was calculated to be one or two (average was 1.4), while that of p40 was about ten.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our previous study (31), p40 was suggested to be a hyperphosphorylated form of P protein based on the observation of its relatively much higher specific radioactivity than that of p37 in the double radiolabeling experiments with [ 32 P]orthophosphate and [ 3 H]leucine. The number of phosphate groups in each p37 molecule was calculated to be one or two (average was 1.4), while that of p40 was about ten.…”
Section: Discussionmentioning
confidence: 99%
“…For expression of the rabies virus P protein in E. coli, we used a fulllength P cDNA clone which was transferred into the NdeI site of an inducible expression vector pET3a (Novagen) as described previously (31). Expression was done in E. coli BL21(DE3) pLysS (Novagen) by adding isopropyl-β-D-thiogalactopyranoside (IPTG) at a final concentration of 1 mM according to Studier et al (30).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations